Abordagem da transitividade em um livro didático de língua portuguesa e sugestão de atividade com enfoque sistêmico- funcional - Bitencurt, Simone Marci (2025)
This research aims to examine how transitivity is addressed in linguistic analysis activities and theoretical explanations within a Portuguese language textbook and to propose an activity for teaching transitivity from a Systemic-Functional perspective. This study employs a qualitative interpretative approach, grounded in the theoretical framework of Systemic-Functional Linguistics by Halliday and Matthiessen (2014) and the work of Martin and Rose (2008), and Rose and Martin (2012) for activity development focused on linguistic transitivity analysis from the Sydney School perspective. The analyzed corpus consists of the 7th-grade Portuguese language textbook from the "Português: conexão e uso" series by Delmanto and Carvalho (2018), approved by PNLD for the 2020-2023 period. Two sections from Unit 6, which address the study of transitivity, were selected due to their relevance to the research. The data collection involved the following procedures: (1) examination of the theoretical-methodological foundation in the Teacher's Manual; (2) identification of the text, language, and context conceptions in the Teacher's Manual; (3) assessment of the stated approach to teaching the Portuguese language in the Teacher's Manual; (4) discussion of the collected data. The text analysis and activity development procedures were conducted in two stages. The first included: (1) text segmentation into clauses; (2) identification of clause components and classification of clause types; (3) identification and description of participant roles in each clause; (4) identification and description of circumstantial roles in the text. The stage involved the following aspects: (1) recognition and description of clause components; (2) understanding the different types of processes that construct sentences; (3) identification and description of participant roles in the text; (4) identification and description of circumstantial roles in the text. The analyses of the textbook sections showed that there is an attempt to teach transitivity based on functionalism. However, there are indications of Normative Grammar in the theoretical explanations and activities used in the textbook to teach transitivity. The concept of text expressed in the Teacher's Manual is that of a unit with meaning and the concept of context is not explicit, however its relevance for understanding the text is recognized. Finally, the suggested activity that accompanies this study presents itself as a possibility for teaching Portuguese from a perspective different from Normative Grammar, which is why it requires a methodology focused on the meaning constructed by the linguistic forms in the text.